Cognitive, Affective, and Spiritual Assessment as well as Psychological Evaluation in Islamic Education - Alfani, Ajeng Khori; Rosyid, Ahmad Sihabudin; Munib, Fathul; Wahyudi, M. Eka; Wardana, Prima Whisnu; Jannah, Siti Roudhotul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This article discusses assessment and psychological evaluation in Islamic education as a holistic process oriented toward the comprehensive development of students’ personalities. Islamic education emphasizes not only the mastery of knowledge but also the development of affective, spiritual, and character dimensions. Therefore, evaluation systems need to integrate Islamic values such as justice, honesty, balance, and moral responsibility with modern educational psychology approaches. The discussion covers principles of evaluation in Islam; cognitive, affective, and spiritual assessment; the implementation of authentic assessment; the use of observational instruments to monitor character development; as well as the importance of validity and reliability in the construction of assessment tools. Authentic assessment is employed to evaluate students’ abilities through real-life practices that reflect the internalization of Islamic values in daily life. The validity and reliability of evaluation instruments are essential to ensure that assessment results are objective and can be scientifically and morally justified. This study is based on issues related to assessment and psychological evaluation in Islamic education, with a focus on five key considerations: principles of evaluation in Islam; cognitive, affective, and spiritual assessment; authentic assessment; observational instruments for character development; and validity and reliability within the Islamic framework. This research adopts a descriptive qualitative method in the form of a literature study, aiming to present findings derived from a review of selected